Multiomics Analysis Identifies SOCS1 as Restraining T Cell Activation and Preventing Graft‐Versus‐Host Disease. Issue 21 (18th May 2022) - Guo, Huidong; Li, Ruifeng; Wang, Ming; Hou, Yingping; Liu, Shuoshuo; Peng, Ting; Zhao, Xiang‐Yu; Lu, Liming; Han, Yali; Shao, Yiming; Chang, Ying‐Jun; Li, Cheng; et al.
Abstract: Graft‐versus‐host disease (GVHD) is a major life‐threatening complication of allogeneic hematopoietic stem cell transplantation (allo‐HSCT). Inflammatory signaling pathways promote T‐cell activation and are involved in the pathogenesis of GVHD. Suppressor of cytokine signaling 1 ( SOCS1 ) is a critical negative regulator for several inflammatory cytokines. However, its regulatory role in T‐cell activation and GVHD has not been elucidated. Multiomics analysis of the transcriptome and chromatin structure of granulocyte‐colony‐stimulating‐factor (G‐CSF)‐administered hyporesponsive T cells from healthy donors reveal that G‐CSF upregulates SOCS1 by reorganizing the chromatin structure around the SOCS1 locus. Parallel in vitro and in vivo analyses demonstrate that SOCS1 is critical for restraining T cell activation. Loss of Socs1 in T cells exacerbates GVHD pathogenesis and diminishes the protective role of G‐CSF in GVHD mouse models. Further analysis shows that SOCS1 inhibits T cell activation not only by inhibiting the colony‐stimulating‐factor 3 receptor (CSF3R)/Janus kinase 2 (JAK2 ) /signal transducer and activator of transcription 3 (STAT3 ) pathway, but also by restraining activation of the inflammasome signaling pathway. Moreover, high expression of SOCS1 in T cells from patients correlates with low acute GVHD occurrence after HSCT. Overall, these findings identify that SOCS1 is critical for inhibiting T cell activation and represents a potential target for the attenuation of GVHD. Abstract : Granulocyte‐colony‐stimulating‐factor (G‐CSF) activates signal transducer and activator of transcription 3 (STAT3) by the colony‐stimulating‐factor 3 receptor (CSF3R), then phosphorylated STAT3 enters into nucleus and upregulates suppressor of cytokine signaling 1 ( SOCS1 ) by reorganizing chromatin structure around the SOCS1 locus. Activating SOCS1 prevents T‐cell activationand graft‐versus‐host disease by inhibiting CSF3R, STAT3, and NOD‐, LRR‐ and pyrin domain‐containing protein 3 (NLRP3) inflammasome activation.